The Feasibility of an E-Module Integrating SDGs 2.4 Based on Problem-Based Learning (PBL) for Ownership of Learning Skills - Anggun Septi Rahayu; Balqis Balqis (ISEJ : Indonesian Science Education Journal, 2025)
This study aims to develop and test the feasibility of an e-module integrating SDGs 2.4 based on the Problem-Based Learning (PBL) model to enhance students' ownership of learning skills. This research is a Research and Development (R&D) study. The development model used in this research is the Lee & Owens development model. The e-module is designed using digital platforms such as Google Sites and Canva, and integrates various learning resources such as multimedia, educational videos, scientific articles, and quizzes. Data collection was carried out through a validation questionnaire involving subject matter experts, media experts, and biology education practitioners to assess the feasibility of the e-module. The questionnaire instrument uses a Likert scale with five evaluation categories. The collected data was analyzed using descriptive quantitative analysis to provide an overall evaluation of the results. The feasibility test results show that the e-module meets high feasibility standards, with a material feasibility score of 100% and a media feasibility score of 99.71%. The results of the learning tools experts’ validation showed an average score of 99%, and the feasibility test by biology education practitioners achieved a score of 97.5%. The e-module is deemed highly feasible for use. These findings indicate that digital learning tools such as e-modules can significantly enhance student engagement and motivation, making learning more effective and relevant to real-world challenges.